Perspective Analysis of Unwaha Jombang Students in Learning Religion Through Social Media "Facebook" - Aufia Aisa; Izzatul Mumtazah Rofiq (SCHOOLAR: Social and Literature Study in Education, 2022)
Social media has become a trend among teenagers, especially Facebook, therefore it can be used as an alternative media for learning Islam through social media Facebook. This study aims to: The effectiveness of learning Islam through social media facebook, to analyze the opinions of Unwaha Jombang students in learning religion through facebook. And to know how to find valid sources when using social media. The approach used to achieve the above objectives is to use a quantitative research approach with the type of field study research. In collecting data, the author uses the method of questionnaires, interviews, and documentation. Based on the research above, the researcher can conclude about "The Perspective Analysis of Unwaha Jombang students in learning Islam on Facebook can be concluded as follows: the use of Facebook social media according to the perspective of Unwaha Jombang students is not effective. Because according to students studying Islam through the Facebook application is not necessarily clear, so students tend to use Facebook as entertainment or as a means of communication only.